Valeological education of preschoolers. - Chernykh E. G., Penkina N. A., Sokolovskaia E. S., Zakharchenko A. S. (The health of participants in the educational process: modern challenges and solutions, 2025)
The article examines the importance of valeology as the basis for the formation of a healthy lifestyle in preschoolers. The main aspects of valeological education, its impact on the physical, mental and social development of children are discussed. The main goal of valeological education is to create a child's conscious attitude to their health, to form stable habits for a healthy lifestyle and to understand the role of health for a successful and happy future.
Keywords: детский сад; дошкольное образование; здоровый образ жизни; healthy lifestyle; preschool education; kindergarten; валеология; валеологическая культура; valeology; valeological culture